Implementsi Buku Panduan Praktis Al-Imrithy Dalam Meningkatkan Pembelajaran Qowa’id Peserta IHFAD Pondok Pesantren Darussalam Blokagung Banyuwangi - Fitriah Anggraeni, Restu; Nawawi, Mahbub (Universitas KH. Mukhtar Syafaat, 2024)
The aim of this research is to determine the implementation of the Al-Imrithy practical guidebook among Ihfad Pondok Pesantren Darussalam Blokagung Banyuwangi participants as well as supporting and inhibiting factors in learning qawaid. This research uses descriptive qualitative research methods. Collection techniques by means of observation, interviews and documentation. Data analysis using data reduction, presentation and conclusion processes. The results of this research are that the learning activities of Ihfad Pondok Pesantren Darussalam Blokagung participants have three types of main material, namely Jurumiyyah, Al-Imrithy and Alfiyyah. This activity is yaumiyyah or carried out every day except Tuesday night and this activity focuses more on basic understanding of nadzam and key words. The supporting factors in learning qawaid nadzam Al-Imrithy for Ihfad participants are high enthusiasm and strong determination, both from administrators, mentors and participants. In addition, the positive impact caused by the mnemonic method is that it makes it easier for participants to understand and process nadzam. Meanwhile, the inhibiting factors were the relatively short time, inadequate space, and a busy situation, which made the Ihfad participants feel less than optimal in receiving explanations from the supervisor.